Audit Lag di Era Digitalisasi Pada Sektor Energy Di Indonesia - Christina Saputri; Enny Susilowati Mardjono (Universitas Muhammadiyah Metro, 2025)
This study examines examines the effect of profitability, liquidity level, and company size on the time lag in issuing audit reports. The sample consisted of energy companies listed on the Indonesia Stock Exchange, selected through a purposive sampling method based on specific criteria. The study employs a quantitative method by examining secondary data from the Indonesia Stock Exchange. 159 observation data were analyzed using multiple linear regression from 2020 to 2023. The study demonstrates that (a) profitability affects the audit period in financial reporting, (b) liquidity has no effect on the audit period in financial reporting, and (c) company size has no effect on the audit period in financial reporting. The study aims to comprehend the factors influencing the audit periods in financial reporting within the energy sector.